2005
DOI: 10.1783/1471189054483915
|View full text |Cite
|
Sign up to set email alerts
|

Home self-administration of misoprostol for medical abortion up to 56 days' gestation

Abstract: Objective Studies from the USA have suggested the feasibility and acceptability of home medical abortion, however the issue has not been addressed in the UK. This study aimed to assess the feasibility, efficacy and acceptability of home self-administration of misoprostol for medical abortion up to 56 days' gestation. Methods Mifepristone 200 mg was given orally in hospital under nursing supervision. Women were provided with misoprostol tablets 600 µg and advised to take them sublingually 36-48 hours later. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…Research suggests that women self-managing first trimester TOP have varied experiences [2][3][4] but are no more likely to re-attend with complications than those treated in hospital. 5 Although a growing body of literature suggests that self-management is acceptable to women, 2,[6][7][8][9][10][11][12][13][14][15][16][17] there is a need to monitor and understand women's needs around this model of provision, to facilitate provision of the best possible support. Our research contributes to this understanding, by examining details of women's experiences of self-management ≤63 days, of which to date, relatively little is known.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that women self-managing first trimester TOP have varied experiences [2][3][4] but are no more likely to re-attend with complications than those treated in hospital. 5 Although a growing body of literature suggests that self-management is acceptable to women, 2,[6][7][8][9][10][11][12][13][14][15][16][17] there is a need to monitor and understand women's needs around this model of provision, to facilitate provision of the best possible support. Our research contributes to this understanding, by examining details of women's experiences of self-management ≤63 days, of which to date, relatively little is known.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials from Canada, 7 Turkey 8,9 and the United States 10,11 report rates of complete abortion ranging from 91% to 98% for pregnancies up to 9 weeks when misoprostol is administered at home (Appendix A, available at: http://www.mariestopes.org/documents/Home-based%20 Medical-Abortion-Systematic-Review-Appendix.pdf ). Observational studies [12][13][14][15][16][17][18][19][20] have also shown that home-based medical abortion is well accepted and effective, with 86-98% of women reporting satisfaction with the method and complete abortion achieved in 87% to 98% of cases. However, none of these studies has compared home-based medical abortion with clinic-based protocols.…”
Section: Introductionmentioning
confidence: 99%
“…6,12,17,18 This may reflect the small numbers of patients seen so far and our own learning curve. The uptake of telephone advice has amounted to a handful of calls and only one patient was admitted on the day of the misoprostol treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Other investigators 12,15,16 have demedicalised medical termination by allowing the patient to self-treat with misoprostol at home rather than in hospital. Under the terms of the Abortion Act 1967, all treatment for abortion should be given in licensed premises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation